The Role of Working Women in Investment Decision Making in the Family in India - Manish Sharma; Hima Bindu Kota (Australasian Accounting, Business and Finance Journal, 2019)
The contribution of Indian women in family, businesses and society is today being recognized. The role of women in the family decisions is also increasing with the change in demographics as more women are now participating in economic activities. With the change in education, employment and contribution in the earnings of the family, her say in the family decisions are increasing. When it comes to the investment decisions, women tend to be risk averse, have conservative attitude, lower levels of financial knowledge, lack of confidence and dependent on guidance from others as suggested by different researches worldwide. The role of husband becomes particularly important for women while choosing investment products or taking investment decisions. This article attempts to highlight the role of women in investment decision making in the family and further examines the role of a male spouse on the investment decisions. The objectives of the study were to examine the behavior of working women while taking investment decisions; and to identify the extent to which the investment decisions of the working women are influenced by the spouse/husband. The article further highlights that, when it comes to investment decisions, both husband and wife share responsibility for making investment decisions. There are investment products like Bank deposits, 5 year tax saving FDs, precious metals, public provident fund, national pension system, post office saving schemes, mutual funds, life insurance, and commodities, where the influence of women is stronger than their male spouse. The influence of a male spouse is stronger in products like real estate, company deposits, debentures or bonds, pension schemes, equity shares and derivatives.
Keywords: India; Financial Planning; wealth management; Women; Role of Women; Investment Decisions; Family; Investment Decision Making